ORGANIZATIONAL METHODICAL BASES OF THE CREDIT-MODULE SYSTEM IN INCREASING THE EFFICIENCY OF INDEPENDENT EDUCATION OF INITIAL TRAINING BEFORE THE CONVOCATION - Axmedova Malohat Ergashevna; Abdullayev Mustafo Qalandar o’g‘li (Galaxy International Interdisciplinary Research Journal, 2023)
The current state and prospects of transition to the credit-module system in the development of students’ independent educational tasks in the organization of pre-vocational primary training and its teaching, the credit-module of higher education institutions based on the best world experiences system principles, learner, recognition of educational results. It is desirable to create the possibility of independent formation of the educational trajectory and academic mobility, the accumulation of grades, the interest of professors and students in the organization and teaching of primary training before the convocation, as well as the introduction of a clearly defined evaluation system it is justified.